Implementing and evaluating integrated care models for non-communicable diseases in fragile and humanitarian settings - Lavanya Vijayasingham; Éimhín Ansbro; Carla Zmeter; Linda Abou Abbas; Benjamin Schmid; Leah Sanga; Lars Bruun Larsen; Sigiriya Aebischer Perone; Pablo Perel (Elsevier, 2024)
In this commentary, we advocate for the wider implementation of integrated care models for NCDs within humanitarian preparedness, response, and resilience efforts. Since experience and evidence on integrated NCD care in humanitarian settings is limited, we discuss potential benefits, key lessons learned from other settings, and lessons from the integration of other conditions that may be useful for stakeholders considering an integrated model of NCD care. We also introduce our ongoing project in North Lebanon as a case example currently undergoing parallel tracks of program implementation and process evaluation that aims to strengthen the evidence base on implementing an integrated NCD care model in a crisis setting.